Protective Effect of Alginate Extraction of Brown Algae on MicroRNAs in Type 1 Diabetes of Rats - Mohammad Sharifzadeh; Aghil Esmaeili-Bandboni; Mohammadreza Emami; Abbas Mirshafiey; Mohammad Hassan Javanbakht (International Journal of Nutrition Sciences)
Background: MicroRNAs expressions that are known as Posttranscriptional repressors of gene expression in animals and plants have an important role in diabetic consequences and pathogenesis. This research aimed to investigate the expression of miR-34a, miR-126, and miR-125a-5p levels for diagnosis of diabetes, and the effect of α-L-guluronic acidand β-D-mannuronic acid supplementation on expression patterns of these MicroRNAs in diabetic rats.Methods: Total MicroRNAs levels were measured by Quantitative reverse transcription polymerase chain reaction (qRT-PCR) method. Body weight, fasting insulin level, food intake and Vitamin D level in four groups were also assessed after 4 weeks.Results: The analyses illustrate marked declines in expression of miR-126 (p=0.009) and miR-125a-5p (p=0.019) levels in the control diabetic group when compared to the control healthy group. Expression levels of miR-126 (p=0.026) and miR-125a-5p (p=0.041) were upregulated considerably in diabetic rats after treatment with β-D-mannuronic acid and α-L-guluronic acid, respectively.Conclusion: These results suggest that use of miR-126 and 125a-5p is a sensible criterion for diagnosing diabetes. β-D-mannuronic acid is also considered a new therapeutic agent to correct disturbances in the MicroRNAs profile of diabetic rats.